SURAT KABAR âSOEARA BONDJOLâ DI MEDAN : Studi Sejarah Pers Komonitas di Sumatera Timur Tahun - Kinul, Kinul; Naldi, Hendra; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
Generally, this research is purposed to see the history of âSOEARA BONDJOLâ IN MEDAN : A Study Of Pers Community In East Sumatera 1919-1925. Moreover, the purpose of this research is to know history experiences (pre-education) which stimulate the appreance of Soeara Bondjol newspaper. It responded reader of society that time and it was exist among massa media in Medan.Furthermore, the research method is history method. Researcher used two kinds of data, they are primary and secondary data. The primary datawas Soeara Bondjol newspaper 1919-1925 edition and Besluit. Books, journals and magazines were the secondary data whch are used in this research. In interview study researcher did an interview with resources who were convenient for this researcher.The findings of this researchshown that Soeara Bondjol newspaper had hometown base (it was especially for minang people in Bondjol. It published in Medan by Setia Bondjol. Organization. Its development involved physical appearance and content. Indevelopmetal period, Soeara Bondjol was consisted of two periods, such as first periode (1919-1921) and movement period (1922-1925) the regrssionof this newspaper was caused by financial problem. Soeara Bondjol was one of unit actinity from Setia Bondjol communitywhich established in Medan, November 22th 1914. âSetia Bondjolâ is a commonications media of Bondjol society. The purpose of theis newpaper is thevelopment for Bondjol, Negeri Nan Tigo Laras Rajo Nan Ampek Selo. It gave a news or informations about activity of Setia Bondjol community and its problems. There were so many changes and development in this period starting from beginning until the end. It can be proved by viewing its cover rubrication and its financial.